Picky eating and positive outcomes from healthcare interactions : a narrative analysis of interviews with parents identifying pathways to progress : an appreciative inquiry into positive healthcare provider appointments by parents help-seeking for their child’s picky eating in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Yeabsley, J. K. (Massey University, 2024)
With estimates of clinically diagnosed picky eating prevalence greater annually than that of autism spectrum disorder in the paediatric population and negative outcomes for those children experiencing feeding issues, it is unsurprising research in the area is increasing. However, globally absent is qualitative exploration of parents’ experiences in primary care when help-seeking for their child’s picky eating. Prior research, when touching on the subject, primarily documents lack of support. This study therefore sought to establish via an appreciative inquiry what positive medical experiences look like, and whether affirmative appointments lead to good outcomes. Eleven parents participated in semi-structured interviews, with Wong and Breheny’s (2018) three levels of narrative analysis employed to explore the data. The key finding was evidence of a clear, three-part structure across the narratives, consisting of parental management of picky eating, the positive appointment with the doctor, and the outcomes from that interaction. Within these, four key themes were explored. First, the challenge of defining picky eating and the impact on decision making for participants. Second, the effect on participant behaviour of wider social discourses of motherhood and its interaction with public health messages. Third, the importance of the relationships between doctor–parent and doctor–child. Finally, that doctors were limited by a range of factors in the care they could provide. The study showed that positive experiences are characterised by personable, caring doctors but that picky eating was neither well-understood nor resolving it prioritised.
Keywords: 520304 Health psychology